Hemispheric assymetries in the visual processing of spatial frequencies of facial emotional expressions - Saunoriūtė-Kerbelienė , Silvija; Rukšėnas , Osvaldas; Benson , Philip J. (Psichologija, 2000)
This paper examines two aspects of the lateralisation of cognitive function. A same-different reaction time paradigms was used to characterize perceptual processing in each visual field. Images were degraded using low-pass filtering to exclude ranges of high frequencies. ln this experiment, psychophysical procedures used facial expression images as a carrier for spatial frequency information. Observers had to judge whether two sequentially presented images showed the same emotion, irrespective of identity gender and spatial frequency content. Reaction time and accuracy measures showed that lower frequency information was processed better in the left visual field (right hemisphere). When higher frequency cues were available, both hemispheres processed stimuli equally well. In addition, some expressions were processed mare rapidly or mare accurately in a particular visual field.